Influence of molar mass distribution and long-chain branching on strain hardening of low density polyethylene - Stadler, Florian; Kaschta, Joachim; Münstedt, Helmut; Becker, Florian; Buback, Michael (Rheologica Acta, 2009)
Low-density polyethylenes (LDPE) were synthesized in a laboratory-scale autoclave under high pressure. These samples were found to possess a high molar mass tail, resulting in a distinctly bimodal molar mass distribution and a lower concentration of long-chain branching than typical of commercial LDPEs. Rheological experiments in elongation showed that these samples exhibit a very pronounced strain hardening, which could be favorable for distinct processing operations. Although the samples have a rather high molar mass (M(w) = 2...4 x 10(6) g/mol), their zero shear-rate viscosities eta(0) and their shear thinning behavior are still in a range, where thermoplastic processing is possible. Aqualitative understanding of the experimental results is tried by the model of the Cayley tree.
Keywords: Low-density polyethylene; Autoclave process; Molar mass distribution; Long-chain branching; Elongational rheology; Viscosity functions